The Impact of Culture on Creativity - Chua, Roy Y. J.; Roth, Yannig; Lemoine, Jean-François (Administrative Science Quarterly, 2015)
This paper advances a new theoretical model to understand the effect of culture on creativity in a global context. We theorize that creativity engagement and success depend on the cultural tightness—the extent to which a country is characterized by strong social norms and low tolerance for deviant behaviors—of both an innovator’s country and the audience’s country, as well as the cultural distance between these two countries. Using field data from a global online crowdsourcing platform that organizes creative contests for consumer-product brands, supplemented by interviews with marketing experts, we found that individuals from tight cultures are less likely than counterparts from loose cultures to engage in and succeed at foreign creative tasks; this effect is intensified as the cultural distance between the innovator’s and the audience’s country increases. Additionally, tight cultures are less receptive to foreign creative ideas. But we also found that in certain circumstances—when members of a tight culture do creative work in their own or culturally close countries—cultural tightness can actually promote creativity success. This finding implies that some degree of convergent thinking as engendered by tight cultures could be beneficial for creativity, challenging the dominant view in creativity research that divergent thinking is a prerequisite for creative performance.